Disruption in the Regulation of Immune Responses in the Placental Subtype of Preeclampsia - Geldenhuys, Janri; Rossouw, Theresa Marie; Lombaard, Hendrik Andries; Ehlers, Marthie Magdaleen; Kock, Marleen Magdalena (Frontiers in Immunology, 2018)
Pre-eclampsia is considered a maternal adaptive response to an ischemic placental environment, impacting fetal growth and pregnancy outcome. Inflammatory immune responses have been linked to metabolic and inflammatory disorders as well as reproductive failures. In healthy pregnancy, immune regulatory mechanisms prevent excessive systemic inflammation. However, in pre-eclampsia, the regulation of immune responses is disrupted as a result of aberrant activation of innate immune cells and imbalanced differentiation of T helper cell subsets creating a cytotoxic environment in utero. Recognition events that facilitate immune interaction between maternal decidual T cells, NK cells and cytotrophoblasts are considered an indirect cause of the incomplete remodeling of spiral arteries in pre-eclampsia. The mechanisms involved include the activation of immune cells and the subsequent secretion of cytokines and placental growth factors affecting trophoblast invasion, angiogenesis and eventually placentation. In this review, we focus on the role of excessive systemic inflammation as the result of a dysregulated immune system in the development of pre-eclampsia. These include insufficient control of inflammation, failure of tolerance towards paternal antigens at the fetal-maternal interface and subsequent over- or insufficient activation of immune mediators. It is also possible that external stimuli, such as bacterial endotoxin, may contribute to the excessive systemic inflammation in pre-eclampsia by stimulating the release of pro-inflammatory cytokines. In conclusion, a disrupted immune system might be a predisposing factor or result of placental oxidative stress or excessive inflammation in pre-eclampsia. Pre-eclampsia can thus be considered a hyper-inflammatory state associated with defective regulation of the immune system proposed as a key element in the pathological events of this disorder.